2015
DOI: 10.3109/10799893.2015.1041645
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of AuroraA-TPX2 by novel natural inhibitors: molecular dynamics-based mechanistic analysis

Abstract: We report two natural compounds as potential drugs leads for the disruption of this complex. These ligands show a preferable docking score and have many drugs like properties within in the range of 95% of known drugs. The study provides evidence that CTOM and TTOM can efficiently inhibit the TPX2-mediated activation of Aurora A. Thus, it paves way for an elaborate investigation and establishes the importance of computational approaches as time- and cost-effective techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…More interestingly, these PTMs can be used to design original inhibitory strategies different from those targeting the kinase active site. The binding of TPX2 to Aurora-A for instance has been targeted to search for Aurora-A inhibitor [107]. This kind of approach targeting PTMs offers broad prospects for specific inhibition of Aurora kinases.…”
Section: Resultsmentioning
confidence: 99%
“…More interestingly, these PTMs can be used to design original inhibitory strategies different from those targeting the kinase active site. The binding of TPX2 to Aurora-A for instance has been targeted to search for Aurora-A inhibitor [107]. This kind of approach targeting PTMs offers broad prospects for specific inhibition of Aurora kinases.…”
Section: Resultsmentioning
confidence: 99%
“…Targeting of the mitotic spindle checkpoint, which induces massive aneuploidy and severe chromosome segregation errors, is being considered for developing new therapeutic strategies for selectively eliminating highly proliferative cancer cells [ 41 44 ]. Since TPX2 plays an essential role in mitotic spindle apparatus and subsequently cell division and tumor growth via binding to Aurora-A, many researchers focus on identifying antagonists to blockade this interaction [ 45 ]. Our findings of the regulation of TPX2 expression by Hh signaling provide a novel approach to suppress TPX2 via decreasing its expression level rather than its activity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, molecular dynamics (MD) simulations based studies have demonstrated great potential as a substitute for investigations in understanding the dynamical aspects of protein-ligand interaction, protein folding, and also protein-protein interaction [ 22 30 ]. In the present study, to gain insights into the effects of mutations (K753E, L768S and V773L) on the binding strength of lapatinib, MD simulations of the kinase domain of HER-2 (wild and mutants) in complex with the lapatinib were performed.…”
Section: Introductionmentioning
confidence: 99%